1997
DOI: 10.1016/s0014-5793(97)01435-x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and characterisation of the RET proto‐oncogene 5′ flanking region: analysis of retinoic acid responsiveness at the transcriptional level

Abstract: The RET proto-oncogene encodes a receptor tyrosine kinase expressed during neural crest development. RET expression is enhanced in vitro by several differentiating agents, including retinoic acid (RA), which up-regulates RET expression in neuroblastoma cell lines. In the present work we sequenced and analysed a 5 kbp genomic fragment 5' to RET. Three deletion fragments of this region were tested for their RA inducibility in transient transfection assays and failed to support the hypothesis of a direct transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 60 publications
3
23
0
Order By: Relevance
“…For the induction of GDNF responsiveness in cultured SCG neurons from E17 rats, RA markedly induced the expression of ligandspecifying receptor component GFR␣-1 and increased the efficacy of GDNF-triggered Ret tyrosine phosphorylation. Effect of RA on the upregulation of Ret expression in cultured SCG neurons was rather small, although the significant ability of RA to upregulate the expression of Ret in tumorigenic neuroblastoma cells has been reported previously (Tahira et al, 1991;Bunone et al, 1995;Patrone et al, 1997). The expression of Ret starts from the early stage of neural crest development (Lo and Anderson, 1995;Tsuzuki et al, 1995;Durbec et al, 1996) and continues even after transfer to in vitro culture system, as shown in this study.…”
Section: Discussionsupporting
confidence: 71%
“…For the induction of GDNF responsiveness in cultured SCG neurons from E17 rats, RA markedly induced the expression of ligandspecifying receptor component GFR␣-1 and increased the efficacy of GDNF-triggered Ret tyrosine phosphorylation. Effect of RA on the upregulation of Ret expression in cultured SCG neurons was rather small, although the significant ability of RA to upregulate the expression of Ret in tumorigenic neuroblastoma cells has been reported previously (Tahira et al, 1991;Bunone et al, 1995;Patrone et al, 1997). The expression of Ret starts from the early stage of neural crest development (Lo and Anderson, 1995;Tsuzuki et al, 1995;Durbec et al, 1996) and continues even after transfer to in vitro culture system, as shown in this study.…”
Section: Discussionsupporting
confidence: 71%
“…An additional Pax3 binding site, GTGTGA, has been described for the melanocyte-specific tyrosinase-related protein-1 promoter (30). This consensus sequence is also present in MITF (23) and c-RET (29). The presence of the complimentary sequences TAAT or CAAGG was observed in the STX.…”
Section: Fig 2 Validation Of Representative Pax3 Downstream Target mentioning
confidence: 81%
“…The question of whether RA receptors act by binding to enhancers in Ret regulatory sequences or by inducing expression of an intermediary transcription factor in ureteric bud cells is unclear. Several candidate RA response elements have been identified in the Ret promoter; however, none of these has been shown to drive RAdependent expression (Grice et al, 2005;Patrone et al, 1997), suggesting that RA might control Ret indirectly. Potential direct activators of Ret include Pax2 (Brophy et al, 2001), Hox genes , Ttf1 (Garcia-Barcelo et al, 2007), Nkx2.1 and Nurr1 (Nr4a2 -Mouse Genome Informatics) (Wallen et al, 2001), all of which are localized in the developing kidney.…”
Section: What Renal Cell Types Are Important For Mediating Ra-dependementioning
confidence: 99%